የተሻሻሉ የመኖ ሰብሎችን በኢትዮጵያ ደጋማና ወይና ደጋ አካባቢዎች አመራረትና አጠቃቀም - Bezabih, Melkamu; Adie, Aberra; Assefa, Getnet; Mekonnen, Kindu; Gebreyes, Million (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Climate Smart Feed and Forage Innovations Training Workshop-Amharic.